Uji Antimikroba Rumput Mutiara (Hedyotis corymbosa) terhadap Bakteri dan Jamur Penyebab Penyakit pada Ternak Unggas - Nurhayati Nurhayati; Madyawati Latief; Heru Handoko (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2006)
An experiment was conducted to determine the activity of pearl grass (rumput mutiara, Hedyotis corymbosa) in inhibiting growth of bacterial and fungi causing diseases in poultry.The current study used 3000 gram of sorted and cleaned pearl grass from dust and other weeds. This study employed sample collection, extraction, fractionation, preparation of medium of Agar and Mueller Hinton Broth, culturing bacterial, antimicrobial test and measuring minimum inhibitory concentrations. Extraction was conducted by maceration of pearl grass with methanol for five days followed by evaporating in vacuo to get methanol extract. The extract was then fractionated by adding hexane or acetic acid and ethyl acetic or sodium bicarbonate or n-buthanol to get fraction of hexsane, acid ethyl acetic, base ethyl acetic, n-buthanol. Each fraction was then tested with microbial test that were Salmonella sp, Escherichia coli, and Candida albicans. The results showed that each fraction at 2 % of concentration could inhibit bacterial growth except for Candida albicans that was not inhibited by any fraction of pearl grass. The minimum inhibitory concentrations was 0.4 – 0.8% (4 mg/ml – 8 mg/ml) indicating that pearl grass fractions were highly active on inhibiting bacterial growth that cause poultry diseases and the inhibiting activity on E. coli was found higher than that on Salmonella sp.